Perilaku sadar gizi dan ketahanan pangan keluarga serta hubungannya dengan status gizi balita di Kabupaten Tanah Laut, Kalimantan Selatan - Rahmadi .; Toto Sudargo; Agus Wijanarka (Alma Ata University Press, 2013)
Background: Act No. 25/2000 about National Development Program and Vision Healthy Indonesia 2010 speciﬁ ed that 80% of Indonesian families become nutrition aware families. The result of survey on nutrition aware families in indicated that in 2006 as much as 52.7% and in 2007 as much as 27.2% of families were not yet nutrition aware. The result of nutritional status monitoring of underﬁ ves (Z-score) showed undernourishment increased from 5.1% in 2004 to 10.1% in 2005.Objective: To analyze association between nutrition aware behavior and food security of the family and nutrition status of underﬁ ves at District of Tanah Laut, Province of Kalimantan Selatan.Method: The study was observational with cross sectional design. The dependentvariable was nutritional status of underﬁ ves (z-score for weight/length); the independent variables were nutrition aware behavior and food security of the family; and the confounding variables were characteristics of the family (parents’ education, number of the family members, knowledge of mothers about nutrition and family income). Subject consisted of underﬁ ves of 6–24 months with as many as 198 underﬁ ves. Data analysis used chi square and double logistic regression (multiple logistic regression) and qualitative analysis with indepth interview for families that were not yet nutrition aware.Result: There were 145 families (73.2%) that were nutrition aware and 53 (26.8%) that were not yet nutrition aware; based on energy consumption 51.1% of families had enough food and 48.9% were undernourished; based on protein consumption 52.5% of families had enough food and 47.5% were undernourished; and children with good nutrition status were 72.6% for boys and 72.8% or girls. There was signiﬁ cant association between nutrition aware behavior and nutrition status of underﬁ ves (p=0.010). The result of logistic regression test showed that there was signiﬁ cant association between the number of family members and food security of the family (p<0.05) with OR=5.516 (95%CI=2.584–11.775). There was signiﬁ cant association between knowledge of mothers about nutrition and food security of the family (p<0.05) with OR=0.486 (95%CI=0.25–0.914).Conclusion: There was no association between nutrition aware behavior and food security of the family based on level of energy and protein consumption. There was signiﬁ cant association (p<0.05) between number of family members and food security of the family based on level of energy and protein consumption. There was signiﬁ cant association between knowledge of mothers about nutrition and food security of the family based on energy consumption. There was no association between parents’ education and family income based on level of energy and protein consumption. There was signiﬁ cant association between nutrition aware behavior of the family and nutrition status of underﬁ ves; however there was no association between food security of the family and nutrition status of underﬁ ves.KEYWORDS: nutrition aware, family characteristics, food security, nutritional status of underﬁ vesABSTRAKLatar Belakang: Undang-undang nomor 25 tahun 2000 tentang Program Pembangunan Nasional dan Visi Indonesia Sehat 2010 menetapkan 80% keluarga menjadi keluarga sadar gizi (kadarzi). Hasil data survei kadarzi pada tahun 2006 dan 2007 didapatkan keluarga yang belum kadarzi 52,7% dan 27,2%. Hasil pemantauan status gizi balita (z-ScoreBB/U) didapatkan status gizi kurang menunjukkan adanya peningkatan, yaitu tahun 2004 sebesar (5,1%), tahun 2005 (9,8%)dan tahun 2006 (10,1%) Tujuan: Untuk menganalisis hubungan antara perilaku sadar gizi dan ketahanan pangan keluarga dengan status gizi balita di Kabupaten Tanah Laut Provinsi Kalimantan Selatan.Metode: Jenis penelitian observasional dengan rancangan cross sectional. Variabel terikat: status gizi balita (z-score BB/TB) dan variabel bebas: perilaku sadar gizi, ketahanan pangan keluarga serta variabel pengganggu: pendidikan orang tua, jumlah anggota keluarga, pengetahuan gizi ibu dan pendapatan keluarga. Subjek penelitian balita usia 6-24 bulan, jumlah 198 balita. Analisis yang digunakan adalah uji chi-square dan regresi logistik berganda (multiple logistic regression) dan didukung analisis kualitatitf dengan indepth interview bagi keluarga belum kadarzi.Hasil: Keluarga sudah kadarzi 145 (73,2%) dan belum kadarzi 53 (26,8%). Indikator kadarzi tentang dukungan keluarga memberikan ASI eksklusif 0-6 bulan paling banyak tidak dilaksanakan. Alasannya adalah setelah melahirkan ASI tidak keluar, susu ibu bengkak dan mengeluarkan darah, hamil lagi, dan alasan pekerjaan. Semua keluarga menggunakan garam beryodium dalam memasak makanan. Keluarga tahan pangan dan tidak tahan pangan berdasarkan tingkat konsumsi energi masing-masing sebesar 47,5% dan 52,5%, keluarga yang tahan pangan dan tidak tahan pangan berdasarkan tingkat konsumsi protein masing-masing sebesar 52,5% dan 47,5% dan status gizi balita hasil z-score BB/TB didapatkan balita gizi baik 72,7% dan gizi kurang 27,3%. Perilaku sadar gizi berhubungan signiﬁ kan dengan ketahanan pangan keluarga berdasarkan tingkat konsumsi energi (p<0,05). Perilaku sadar gizi dan ketahanan pangan keluargaberdasarkan tingkat konsumsi energi dan protein tidak berhubungan signiﬁ kan dengan status gizi balita (p>0,05).Kesimpulan: Perilaku sadar gizi, jumlah anggota keluarga, pengetahuan gizi ibu dan pendapatan per kapita berhubungan signiﬁkan dengan ketahanan pangan keluarga berdasarkan tingkat konsumsi energi, sedangan pengetahuan gizi ibu dan pendapatan per kapita berhubungan signiﬁ kan dengan ketahanan pangan keluarga berdasarkan tingkat konsumsi protein. Perilaku sadar gizi keluarga dan ketahanan pangan keluarga berdasarkan tingkat konsumsi energi dan protein tidak berhubungan dengan status gizi balita (z-score BB/TB).KATA KUNCI: keluarga sadar gizi, karakteritik keluarga, ketahanan pangan, status gizi balita